Lipid Accumulation Product and 25-OH-Vitamin D Deficiency in Type 2 Diabetes (The Review of Diabetic Studies, 2023)
BACKGROUND: Emerging data suggest a link between vitamin D (25(OH)D) deficiency, type 2 diabetes (T2D), and visceral adiposity. The lipid accumulation product (LAP), strictly correlated with abdominal fat depots, is proposed as marker of dysfunctional adiposity. AIM: To verify the association between 25(OH)D levels and LAP in T2D. METHODS: Body mass index (BMI), waist circumference (WC), glucose, HbA1c, lipids, and 25(OH)D were assessed in 420 T2D outpatients and in 150 non-diabetic obese with similar anthropometric characteristics. LAP was computed as the product of sex-specific enlarged WC and triglycerides (TG). RESULTS: In T2D patients, 63.0% showed 25(OH)D deficiency (< 0.001), while in obese patients this prevalence was not significant. In both genders, 25(OH)D was not significantly associated with HbA1c and fasting glucose. Age-adjusted 25(OH)D levels were inversely correlated with BMI (p < 0.001), WC (p < 0.001), and LAP (p < 0.001) in both genders. Metabolic syndrome presented an odds ratio (OR) for 25(OH)D deficiency of 1.6 (1.1-2.5, p = 0.048) in females and 1.7 (1.2-2.7, p = 0.016) in males, while the highest quartile of LAP showed an OR of 2.1 (1.2-3.6, p = 0.019) in females and 3.2 (1.6-6.5, p = 0.02) in males. A similar trend was observed in the obese control group. CONCLUSIONS: In the presence of excess weight, subjects with and without T2D frequently feature low 25(OH)D levels. Subjects with higher LAP exhibit a high risk of 25(OH)D deficiency, suggesting that dysfunctional adiposity is a worsening factor for vitamin D hypovitaminosis.